Softs Skills Teacher Camp of Adventure Training to increase teachers' commitment in Pathani Thailand - Hadi Suyono; Mus-ab Buenae (Universitas Ahmad Dahlan, 2020)
Commitment is needed to overcome various obstacles while teaching in conflict areas. This study aimed to increase teacher commitment in the Pathani conflict area, Southern Thailand, through Soft Skills Teacher Camp of Adventure Training. A quantitative approach using a quasi-experimental method was used in this study. Thirty teachers from six schools with a maximum age of 35 years participated in soft skills training. The Soft Skills Teacher Camp of Adventure Training consists of six sessions on six different soft skills, which are motivation, stress management, creativity, teamwork, communication skills, and leadership. The commitment scale consisting of three aspects: affective commitment, normative commitment, and continuance commitment, was used to collect the data. Paired Sample t-test was used to analyze the data. The result highlighted a significant difference between the pretest and posttest scores of teachers’ commitment in the Pathani, Southern Thailand. These findings imply that the Soft Skills Teacher Camp of Adventure Training increases the commitment of teachers who teach in the Pathani, Southern Thailand.